Large-scale farms and smallholders: Evidence from Zambia - Jann Lay; Kerstin Nolte; Kacana Sipangule (Kiel Institute for the World Economy (IfW), 2018)
In light of the surge in large-scale farms in developing countries, concerns have been raised that smallholders may be negatively affected. There is, however, very little evidence beyond case studies to support these claims. Drawing on nationally representative household data sets and an inventory of large-scale farms in Zambia, this study investigates the relationship between large-scale farms and smallholders. First, we analyse the geographical contexts of wards that host large-scale farms and show that large-scale farms are found in wards with good infrastructure and soil quality. Second, we adopt a difference-in-differences approach to estimate the impacts of large-scale farms on smallholders' area cultivated, maize yields, and access to fertiliser. We find that smallholders in wards with large-scale farms increase their area cultivated and maize yields, but have lower fertiliser usage. This hints at positive spillovers at the extensive and intensive margins but not at improved access to agricultural inputs. It is likely that these results are also driven by the emergence of medium-scale farms in these regions.
Keywords: Q12; Q15; Q18; 330; large-scale farms; yields; smallholders; spillovers; Zambia